2010
DOI: 10.1371/journal.pone.0012209
|View full text |Cite
|
Sign up to set email alerts
|

The Use of P63 Immunohistochemistry for the Identification of Squamous Cell Carcinoma of the Lung

Abstract: IntroductionWhile some targeted agents should not be used in squamous cell carcinomas (SCCs), other agents might preferably target SCCs. In a previous microarray study, one of the top differentially expressed genes between adenocarcinomas (ACs) and SCCs is P63. It is a well-known marker of squamous differentiation, but surprisingly, its expression is not widely used for this purpose. Our goals in this study were (1) to further confirm our microarray data, (2) to analize the value of P63 immunohistochemistry (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
2
46
1
Order By: Relevance
“…However, p63 specificity is not high because p63 can be stained focal and/or weak in some ACs (12,13,16). In our study, p63 positivity was observed in 4 AC cases which had TTF-1(+)/ CK5/6 (-).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, p63 specificity is not high because p63 can be stained focal and/or weak in some ACs (12,13,16). In our study, p63 positivity was observed in 4 AC cases which had TTF-1(+)/ CK5/6 (-).…”
Section: Discussioncontrasting
confidence: 62%
“…Morphological misdiagnosis is more common in biopsy because of more limited tissue than in surgical specimens (5). For accurate diagnosis, immunohistochemistry is usually employed in both surgical and biopsy (10,12,13). The immunohistochemical use of CK5/6, TTF-1 and p63…”
Section: Discussionmentioning
confidence: 99%
“…7 Several recent studies showed that immunostains (and previously electron microscopy 42 ) can reveal the line of differentiation as adenocarcinoma vs squamous cell carcinoma in the majority of large cell carcinomas. 26,36,43,44 The proposed TTF-1/p63 algorithm could be used to determine biological identity within the large cell carcinoma, but this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent insights into the clinical and biological significance of non-small cell carcinoma subtypes, several recent studies have analyzed the utility of various combinations of markers for the distinction of adenocarcinoma and squamous cell carcinoma. These studies were performed in small biopsies, [14][15][16] cytology, 17,23 and tissue microarrays, [24][25][26] and the proposed algorithms include between fourand six-marker panels. Although most studies agree on the inclusion of TTF-1 and p63 in the panel, there is no agreement on the role of additional markers.…”
mentioning
confidence: 99%
“…As a result, LCC contains a heterogeneous mix of entities, which complicates any potential characterization studies or clinical trials. In addition to gene expression-based approaches, [11][12][13][14][15][16][17] multiple studies [18][19][20][21][22][23][24][25][26][27] have shown that LCC can be reclassified as ADC, SQC, or large cell neuroendocrine carcinoma by immunohistochemistry. The widespread use of immunohistochemistry in diagnostic practice may explain the decreasing incidence of LCC.…”
mentioning
confidence: 99%